Evaluating feedback frequency preference and its relation to task performance. - Thibodeaux, Janea J.; Taylor, Pierce M.; Bacotti, Janelle K.; Morris, Samuel L. (Journal of Applied Behavior Analysis (John Wiley & Sons, Inc.))
Many researchers have evaluated how characteristics of feedback may influence trainee performance, but relatively little attention has been allocated to directly assessing trainee preference for feedback characteristics and its relation to performance. Thus, the primary purpose of this study was to use a within‐subject experimental design to directly assess trainee preference for the frequency of feedback and its relation to task performance. A secondary objective was to evaluate how trainee preferences varied across specific task components based on component complexity. Thirty‐five undergraduate students completed two arbitrary tasks and were given the opportunity to request feedback after each component of the task. For 85.71% of our participants, an inverse relation was observed between preference for feedback frequency and task performance. Participants requested feedback less often as performance improved. Feedback preferences also varied with the complexity of each component of the task. Implications for training, supervision, and feedback practices are discussed.